Limited Effect of 60-Days Strict Head Down Tilt Bed Rest on Vascular Aging - Möstl, Stefan; Orter, Stefan; Hoffmann, Fabian; Bachler, Martin; Hametner, Bernhard; Wassertheurer, Siegfried; Rabineau, Jérémy; Mulder, Edwin; Johannes, Bernd; Jordan, Jens; Tank, Jens (Frontiers in Physiology, 2021)
Background Cardiovascular risk may be increased in astronauts after long term space flights based on biomarkers indicating premature vascular aging. We tested the hypothesis that 60 days of strict 6° head down tilt bed rest (HDTBR), an established space analog, promotes vascular stiffening and that artificial gravity training ameliorates the response. Methods We studied 24 healthy participants (8 women, 24–55 years, BMI = 24.3 ± 2.1 kg/m2) before and at the end of 60 days HDTBR. 16 subjects were assigned to daily artificial gravity. We applied echocardiography to measure stroke volume and isovolumetric contraction time (ICT), calculated aortic compliance (stroke volume/aortic pulse pressure), and assessed aortic distensibility by MRI. Furthermore, we measured brachial-femoral pulse wave velocity (bfPWV) and pulse wave arrival times (PAT) in different vascular beds by blood pressure cuffs and photoplethysmography. We corrected PAT for ICT (cPAT). Results In the pooled sample, diastolic blood pressure (+8 ± 7 mmHg, p < 0.001), heart rate (+7 ± 9 bpm, p = 0.002) and ICT (+8 ± 13 ms, p = 0.036) increased during HDTBR. Stroke volume decreased by 14 ± 15 ml (p = 0.001). bfPWV, aortic compliance, aortic distensibility and all cPAT remained unchanged. Aortic area tended to increase (p = 0.05). None of the parameters showed significant interaction between HDTBR and artificial gravity training. Conclusion 60 days HDTBR, while producing cardiovascular deconditioning and cephalad fluid shifts akin to weightlessness, did not worsen vascular stiffness. Artificial gravity training did not modulate the response.